Five-year epidemiology of liquefied petroleum gas-related burns. Issue 1 (February 2018) - Jin, Ronghua; Wu, Pan; Ho, Jon Kee; Wang, Xingang; Han, Chunmao
Highlights: LPG-related burns have increased over recent years and have become a serious public health issue. This study details the epidemiology of LPG-related burns and their probable risk factors. Most LPG-related burns resulted from gas leak and occurred at home. Comprehensive medical insurance may improve patient outcomes. This study will assist in planning effective precautions to reduce LPG-related accidents. Abstract: Background: The incidence of liquefied petroleum gas (LPG)-related burns has increased over recent years, and it has become a serious public health issue in developing countries such as India and Turkey. This paper aims to investigate the epidemiological characteristics of LPG-related burns to provide assistance and suggestions for planning prevention strategies. Methods: A 5-year retrospective study was conducted in patients with LPG-related burns admitted to the Department of Burns & Wound Care Center, Second Affiliated Hospital of Zhejiang University, College of Medicine, between 1st January 2011 and 31st December 2015. Information obtained for each patient included age, gender, education status, occupation, medical insurance, average hospital cost, length of hospital stay, monthly distribution of incidence, place of burns, mechanism of burns, extent of burns, site of burns, accompanying injuries, and treatment outcomes. Results: For the first 4 years (2011–2014), the yearly incidence of LPG-related burns was at approximately 10% of all burns; however, in the fifth year (2015) alone, there was a surge to 26.94%. A total of 1337 burn patients were admitted during this period. Of these, 195 patients were admitted because of 169 LPG-related accidents; there were 11 accidents involving more than one victim. LPG-related burns occurred most frequently in patients aged 21–60 years (73.85%). The majority of injuries occurred from May to August (56.41%), and the most common place was home (83.08%, 162 patients). Gas leak (81.03%) was the main cause of LPG-related burns, followed by inappropriate operation (7.69%) and cooking negligence (2.05%). The mean burn area was 31.32 ± 25.40% of TBSA. The most common sites of burns were the upper extremities (37.47%), followed by the head/face and neck (24.80%) and lower extremities (19.95%). The most common accompanying injuries included inhalation injury (23.59%), shock (8.71%), and external injury (7.18%). The average hospital stay was 22.90 ± 19.47 days (range 2–84 days). Only 48 patients (24.62%) had medical insurance, while 124 patients (63.59%) had no medical insurance. The average hospital cost of the no medical insurance group was significantly higher (p < 0.0001) than that of the medical insurance group. In addition, 72.73% of patients who left against medical advice (LAMA) were uninsured. The number of patients who recovered at our hospital was 165 (84.62%), while 22 patients (11.28%) LAMA. The overall mortality rate was 4.10% (8 patients). Conclusion: Our study shows that the exponential increase in LPG-related burns is alarming. This calls for rigorous precautions. Because gas leak was the main cause of LPG-related burns, any part of LPG stove system that shows signs of weathering should be replaced regularly. In addition, we also found that most of the LAMA patients were uninsured. Thus, comprehensive medical insurance should be involved early in the recovery process to assure a safe and adequate discharge.